Expression and the Unconscious - Feyaerts, Jasper; Vanheule, Stijn (Frontiers in Psychology, 2017)
In the present essay, we aim to develop an expressivist reading of the phenomenon of first-person authority and the adverbial meaning of unconsciousness. In the first part, Wittgenstein’s grammatical remarks on the asymmetry between the first –and third-persons in psychological self-ascriptions are developed as an alternative to detectivist explanations according to which first-person authority is to be regarded as a matter of epistemic accomplishment. In the second part, this expressivist account will be used to propose a non-epistemic analysis of the meaning of unconsciousness. Along the way, a critical discussion will be offered of both Freud’s and Lacan’s respective readings of the unconscious. Regarding the latter, we will reject the idea that the concept of the unconscious (i) necessitates the introduction of a (Cartesian) ‘subject of the unconscious’ and (ii) could be deduced from the paradoxes of first-personal reference. In our conclusion, we outline an alternative conception of unconsciousness as not being a matter of something which I qua epistemic subject fail to acknowledge, but of something which I qua speaker seem unable to do.